Effectiveness Of The Emo Demo Module On Malaria Prevention Behavior In The Working Area Of The Sioban Community Health Center, Mentawai Islands Regency - Widdefrita; Darwel; Rahmad Sudiyat; Dinda Wahyuni; Erick Zicof (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Malaria remains a serious disease with high morbidity and mortality rates, particularly among vulnerable groups. Ideally, the community should possess the knowledge, attitudes, and behaviors necessary for effective malaria prevention. However, in reality, although most of West Sumatra has achieved elimination, the Mentawai Islands still have higher case rates, indicating the low effectiveness of health education. As a solution, the Emo Demo Module was used as an interactive educational method. The urgency of this research is the importance of improving the effectiveness of education to reduce malaria cases in endemic areas. The objective of this research is to assess the effectiveness of the Emo Demo Module on the knowledge, attitudes, and actions of the community. The results of the quasi-experimental study in the working area of Sioban Health Center showed an increase in knowledge scores (6.13–7.47), attitudes (42.00–43.80), and actions (41.49–44.27), as well as significant differences before and after the intervention (p ≤ 0.05). This indicates that the Emo Demo Module is effective in improving malaria prevention behavior.